Aperfeiçoamento da gestão comercial de distribuidores na indústria do ramo veterinário pet - Figueiredo, Guilherme Stankuns de Paula (2020)
This study was developed in the environment of IDEXX Laboratories with a focus on the commercial relationship with its distributors. The company is a world leader in the Veterinary Diagnostics segment and is located in over 170 countries. However, it faces challenges of high complexity, especially as regards the flow of information between the parties involved in the negotiations. From the analysis and diagnosis carried out in this study we identified the company's business processes that make it difficult to exchange information, which highlights the existence of information asymmetry. This scenario contributes to the emergence of opportunism and generation of transaction costs in the management of distributors. Therefore, the objective of the study was: to improve information flow in the relationship between IDEXX and its distributors. To achieve this goal, the IDEXX Distributor Portal was designed and developed. It is a digital platform capable of facilitating access to various content essential for the company's business. This is an innovative proposition in IDEXX's indirect sales channel, whose procedures for managing business information are made by automated processes. Notwithstanding the complexity of replacing processes remaining in the company, the first feedbacks from IDEXX internal and external negotiation agents about the implementation of the Portal have been positive. They demonstrated that the developed solution is promising to achieve the proposed objectives and mitigate the impact of information asymmetry as a source of transaction costs in the management of company distributors.